State Subsidies in the Global Economy - Zahariadis, Nikolaos (Palgrave Macmillan US, 2008)
Using figures from European Union members, the volume highlights the conditional effects of globalization, asset specificity, and domestic institutions. Far from being impotent, democratic states face politically powerful pressures to continue to shield social actors from the vagaries of the global market
Keywords: Political science; Political economy; International relations; International economics; Economic policy